IMPLIKASI HUKUM PENDAFTARAN JAMINAN FIDUSIA ONLINE TERHADAP ASAS PUBLISITAS SEBAGAI SALAH SATU CIRI HAK JAMINAN KEBENDAAN - Hermawan, Dofi Yos (JURNAL MEDIA HUKUM DAN PERADILAN, 2019)
The main material of the study due to the law of online fiduciary registration on the principle of publicity as one of the characteristics of material security rights, with the formulation of the problem What is the online registration of fiduciary collateral and What is the result of the legal registration of online system fiduciary guarantees for creditors' publicity rights. The conclusions are as follows: Ratio Legis registration of online fiduciary guarantees, is to improve the service of registration of fiduciary guarantees easily, quickly, and at low cost. Fiduciary registration to guarantee legal certainty and fulfillment of the principle of publicity, but online fiduciary registration involves a notary, only a notary who has a password to access the registration of fiduciary collateral rights, for notary registration of fiduciary insurance impairs public / public access to know that the object belonging to the debtor is burdened with fiduciary collateral for repayment of debt when the debtor is in default. The online system registration fiduciary legal consequences of creditor rights, that the registration of fiduciary guarantees with an online system, against creditors has guaranteed legal certainty by issuing fiduciary certificates, but does not guarantee legal certainty if it turns out that objects fiduciary collateral have been made public, so what happens is that fiduciary is repeated, even though according to Article 17 of the Fiduciary Guaranty Law, re-fiduciary is prohibited. The occurrence of this re-fiduciary was indeed complained by the notary because of the lack of publicity principles regarding the condition of objects being burdened as fiduciary guarantees